Comparison of Market Reaction Between Big Four and Non-Big Four Client on Stock Split Announcements - Ni Putu Yunita Chandra; Dewa Gede Wirama (E-Jurnal Akuntansi, 2024)
This study aims to compare the market reactions to stock split announcements between big four and non-big four clients. This research was conducted using an event study approach. The event window used is seven days of observation around the event date, namely the date of the general shareholders meetings. The market reaction in this study will be proxied by the cumulative abnormal return. The sample determination method uses purposive sampling. The number of research samples is 95 companies, with 44 big four clients and 51 non-big four clients. The data analysis technique used is the independent sample t-test to compare the market reaction between big four and non-big four clients on the announcement of the stock split. The results show that there was no difference in market reaction between big four and non-big four client companies on the stock split announcement.